BLOOD PRESSURE CHANGES DURING THIOPENTONE INDUCTION - Khan, Sham Sher Ali (Journal of Ayub Medical College Abbottabad, 1998)
The study was carried out on total {n = 160) normotensive patients for elective surgical procedures of shorter duration to evaluate the changes in blood pressure using different concentrations and rates of administration of Thiopentone Sodium solutions as induction agent. The study demonstrated that induction with Thiopentone sodium causes a fall in blood pressure, the more concentrated the solution (5 % solution) the more marked is the fall in the blood pressure as compared to the 2.5 % solution. The rapid injection (administered in 30 seconds) causes a rapid and more fall in blood pressure as compared to administered in 1 minute. Atropine premixed with thiopentone causes inconsistent effect on blood pressure as compared to using plain thiopentone sodium, and there is no significant difference between the male and female in their blood pressure response to thiopentone sodium. Meticulous care is needed in the administration of thiopentone along with pre-oxygenation in the normal patients and particularly in those susceptible to its depressant effects such as those with raised blood pressure, elderly and cardiopulmonary compromised situations whereby it should be used slowly and in reduced dosage.